Biodiesel production technology using low-potential energy - Serdyukova Natalya; Shevtsov Alexander (BIO Web of Conferences)
Fatty acid esters obtained as a result of transesterification of vegetable oils or chemical reactions with alcohols are currently the main alternative fuels used in power plants. Since they do not contain aromatic hydrocarbons and sulfur compounds, emissions of CO2, hydrocarbons, carcinogens and carcinogenic substances into the atmosphere are significantly reduced compared to fuels derived from oil. An analysis of the efficiency reserves of the most promising biodiesel production technologies shows the advantages of using supercritical fluids to isolate CO2 from a biodiesel mixture and then separate glycerol, which is associated with environmental cleanliness, safety and energy efficiency. It is shown that the improvement of the technology of supercritical fluids for the production of biodiesel from vegetable oil can be achieved by connecting the OCF absorption-water-ammonia refrigeration unit technology to the general energy supply scheme.